2007
DOI: 10.1080/13548500600580931
|View full text |Cite
|
Sign up to set email alerts
|

The training & support programme for parents of children with ataxia: A pilot study

Abstract: The aim of the study was to evaluate the impact of the Training and Support Programme among parents of children with ataxia. A total of 39 parents expressed an interest in the TSP, 27 (mean age 41; range 25-58) returned baseline questionnaires and completed the study. Twenty-four children (mean age 12.5 years, SD=12.4) received the TSP. Data were collected by self-administered questionnaires mailed to parents immediately before attending the TSP and at 4-month follow-up. Interviews were conducted with 10 paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
2
6
1
1
Order By: Relevance
“…Although generalized self‐efficacy affected care‐work self‐efficacy, care‐work self‐efficacy did not affect generalized self‐efficacy. This result does not lend empirical support to previous studies which have reported that specific therapeutic programs improved generalized self‐efficacy (Barlow et al., 2007; Kelley et al., 1997; Kennedy et al., 2006; Smith, 1989). Mere ego‐engaged experience may not affect generalized self‐efficacy without involvement in a therapeutic program.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Although generalized self‐efficacy affected care‐work self‐efficacy, care‐work self‐efficacy did not affect generalized self‐efficacy. This result does not lend empirical support to previous studies which have reported that specific therapeutic programs improved generalized self‐efficacy (Barlow et al., 2007; Kelley et al., 1997; Kennedy et al., 2006; Smith, 1989). Mere ego‐engaged experience may not affect generalized self‐efficacy without involvement in a therapeutic program.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast, the task‐specific self‐efficacy at Time 1 for sport, music, create, and companionship also affected the generalized self‐efficacy at Time 2. This result lends empirical support to previous studies in which specific therapeutic programs improved generalized self‐efficacy (Barlow et al., 2007; Kelley et al., 1997; Kennedy et al., 2006; Smith, 1989). However, these previous studies did not examine reciprocal causal relationships of task‐specific self‐efficacy and generalized self‐efficacy using panel data analysis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding children with ataxia there is a vivid appeal for specialised, evidence-based treatment [7,14]. We know that parental inclusion through home-based therapy can be effective for motor improvement, as well as for the life quality of children and their families, as reported by the parents themselves [1]. Video gamebased coordination training has also been reported as good means for ataxia improvement [8].…”
Section: Introductionmentioning
confidence: 99%
“…I think I can.を挙げ,自分が成し遂げ たいことを成し遂げることができると信じることは, 成功においてもっとも重要な要素かもしれないと述 べ,20 年以上にわたる膨大な数の自己効力感研究を 要約している。また,竹綱・鎌原・沢崎(1988)によ る 初 期 の 自 己 効 力 感 研 究 の レ ビ ュ ー,Bandura (Bandura, 1995(Bandura, 本明・野口監訳 1997Bandura, 1997 (Ehrenberg, Cox, & Koopman, 1991;Oliver & Paull, 1995 (Betz, Borgen, & Harmon, 1996)が開発された。この Skills Confidence Inventory (Betz et al, 1996) Bandura, 1997;Maddux, 2001; 坂野・前田,2002) 。あ る領域における自己効力感が上昇すると,それに似た 領 域 の 自 己 効 力 感 も 上 昇 す る (Bandura, Adams, Hardy, & Howells, 1980;Brody, Hatfield, & Spalding, 1988) ,さらには言語的課題についての自己効力感が 上昇すれば数学的課題についての自己効力感も上昇す る (Hackett, Betz, OʼHalloran, & Romac, 1990 (Jerusalem & Mittag, 1995山本訳 1997OʼRourke & Hampson, 1999 (Erikson, 1950) ,青年期にはそ の 藤が達成の期待(anticipation of achievement) ・ 仕事見習い(apprenticeship)対労働麻痺(work paralysis)として現れると述べている。Erikson は労働麻 痺について自分の全体的な能力に関する(基本的な 不信感に退行した)深刻な不適合感の論理的な帰結で ある (Erikson, 1959 (Erikson, 1950(Erikson, 仁科訳 1977 (Erikson, 1968) と定義し, 生産的な成人生活への協調的な参加にと って,恒久的な基礎となるもの (Erikson, 1968)と述べている。そして有能感がな いと人間は自分の能力に,劣等感をもち,次第に増 大していく現実の処理に,見合うだけの能力が自分の 中にないのではないかと疑うようになる (Erikson, 1964 (Erikson, 1964 (Erikson, 1968 (Barlow et al, 2007;Kelley et al, 1997;Kennedy et al, 2006;坂野,1989;Smith, 1989 …”
unclassified